Black Soldier Fly (Hermetia illucens) Larvae as a Protein Substitute in Adverse Food Reactions for Canine Dermatitis: Preliminary Results Among Patients - Nuttawan Srifawattana; Yuthana Phimolsiripol; Pinpanit Boonchuay; Kannika Na-Lampang; Promporn Piboon; Sonthaya Umsumarng; Korakot Nganvongpanit (Veterinary Sciences)
Can black soldier fly (BSF) larvae be a protein substitute for managing adverse food reactions (AFRs) in dogs, specifically those with dermatitis? We evaluated BSF larvae’s safety, tolerance, and effectiveness as a novel protein source in dogs with AFRs. Sixteen dogs, including eight healthy controls and eight diagnosed with AFRs, were fed a diet containing BSF larvae for four weeks. Skin conditions, including dermatological lesions and Pruritus Visual Analog Scale (PVAS) scores, and gastrointestinal signs, including relevant clinical signs, stool consistency, and hematological and biochemical parameters, were monitored. No significant gastrointestinal side effects were observed. The control and AFRs groups maintained stable body weights, while stool consistency scores did not change significantly. Moreover, skin reaction data obtained before the study were collected through interviews with the owners. The mean PVAS scores in the AFRs group were significantly higher (p < 0.05) during the self-control period (6.0 ± 1.6) when compared with other periods. However, no significant differences (p > 0.05) were observed between the pre-study baseline (2.0 ± 1.1) and scores at 2 weeks (2.3 ± 1.5) and 4 weeks (2.4 ± 1.2) of feeding with BSF-based food, which indicated that BSF larvae did not exacerbate pruritic symptoms. Hematology and blood chemistry remained within normal ranges in all dogs, indicating no adverse effects on overall health. BSF larvae were well tolerated by AFR-affected and control dogs, with no adverse clinical outcomes. The findings suggest that BSF larvae may offer a better, sustainable alternative protein source for managing AFRs in dogs, particularly in those on hypoallergenic diets. Further long-term studies are needed to confirm these results and assess the broader implications of BSF larvae diets on canine health.